HAKIKAT ILMU DITINJAU SECARA ONTOLOGI EPISTIMOLOGI DAN AKSIOLOGI - Edimizwar; Syamsul Rijal (Jurnal Tarbiyah Almuslim, 2023)
The problem in this research is how the nature of science is examined in terms of ontology, epistemology, and axiology. This study aims to understand and describe the nature of science from the perspectives of ontology, epistemology, and axiology. The approach used in this research is a qualitative approach with the type of research being library research. Data obtained from the research results are analyzed using descriptive methods. Based on the research results, it is found that the nature of science in terms of ontology attempts to prove and examine that the knowledge in question is true and can be proven true. Furthermore, in its discussion, epistemology focuses on the importance of the method or methodology of that scientific knowledge. So, when scientific knowledge is scrutinized through epistemology, the discussion is directed towards the sources used by scientists in developing knowledge and what methods they employ. Then, axiology, where the discussion focuses on the utility or value of that scientific knowledge. In essence, axiology examines whether a scientific knowledge is worthy of development. In summary, ontology talks about the existence of science, epistemology discusses its development, and axiology talks about its value